A comparative study of high school science teachers' performance in the test on understanding science (TOUS) based on some selected variables - Basa, Erlinda Yolo 1942- (1976)
The study compared the performance on the Test on Understanding Science of selected science high school teachers from different schools in Quezon City. Results of the study showed that when mean differences of groups of science teachers are compared, only slight differences are noted. Critical findings were only obtained when physics and biology teachers are compared in areas I and III of the TOUS. Teachers with lesser number of teaching experiences scored better in the TOUS than the more experienced teachers. Non-BSE science teachers scored higher in all areas of the TOUS than the BSE science teachers. Teachers with graduate units in masteral programs in science obtained mean scores slightly higher than the teachers with no graduate units.